Effect of Sodium Dodecyl Benzenesulfonate on the Formation Kinetics of Methane Hydrate - Huang-Yan Ke (11972877); Hui Guo (110581); Wei Ke (158476); Gangfeng Ouyang (1505890) (2022)
At present, the wide applications of gas hydrate in various fields, including gas storage and seawater desalination, are mainly restricted by two limitations: stochasticity of nucleation and slow formation kinetics. Use of surfactants is a way to improve the nucleation and growth rate of hydrate. However, not all surfactants could be considered as effective hydrate promoters, and not all key factors have been discovered. In this paper, the influence of sodium dodecyl benzenesulfonate (SDBS) on the nucleation and growth of methane hydrate was experimentally studied and evaluated in both parallel autoclaves and visible sapphire reactors. The nucleation rate J and lag time τ 0 of hydrate were derived by the penalized maximum likelihood estimation method, and the performance of SDBS as a hydrate promoter was evaluated by these two essential parameters. The p value of the permutation test were calculated for comparison to evaluate the statistical significance of experimental results. In addition, the whole process of hydrate formation and decomposition was recorded with a high-resolution camera installed on a visible sapphire reactor. The results show that SDBS had an obvious kinetic promoting effect on the nucleation rate and average growth rate of methane hydrate, while the total amount of methane consumed was less affected. In the tested range of 110–320 mg/L, the higher the concentration, the stronger the promoting effect. Moreover, the results show that varied molar gas–liquid ratios representing either water- or gas-excess conditions had limited influence on the observed hydrate growth kinetics in the current system. This work provides evidence and insight that a specific surface additive, with experimental validation of its kinetic performance and discovery of key influencing factors, could have the potential to be used in hydrate-based engineering applications.